Disturbi del comportamento alimentare: dagli stili di vita alla patologia Atti del convegno nazionale Firenze, 3 ottobre 1998 - D'Agostini, Corrado (Proceedings e report, 2002)
The Conference, of which the volume constitutes the Proceedings, represented a significant meeting point between psychological and social research experiences (aimed at outlining behaviours and trends), and aspects of clinical and psychiatric field experience. The topics addressed during the Conference concerned the main atypical eating disorders, including Atypical Anorexia Nervosa, Atypical Bulimia Nervosa and Hyperphagic Behaviours associated with other psychological alterations.